Progress on the Industrial Development of Traditional Chinese Medicine Based on Artificial Intelligence - Ren, Kun; Wang, Yannian; Zhao, Yudan; Zhou, Weiyu; Ren, Shumeng; Liu, Jianqiao; Han, Na; Li, Ning (Pharmaceutical Fronts, 2025)
With the increasing demands for drug quality and safety, the traditional Chinese medicine (TCM) pharmaceutical industry is in urgent need of transformation and upgrading. This paper provides an overview of the current application and prospects of artificial intelligence (AI) in the TCM pharmaceutical field. It delves into the specific applications and advantages of AI in various stages such as the selection and harvesting of TCM materials, processing, extraction and purification, formulation, and quality control. The paper points out new directions for the application and development of AI in the TCM pharmaceutical industry, offering a new perspective and approach for the intelligent upgrade of the TCM industry. The aim is to promote the industry's transition toward intelligence and high-quality development, with the hope of providing valuable insights and references for the innovation and upgrade of the entire TCM industry.
Keywords: traditional Chinese medicine; artificial intelligence